Penggunaan Unsur Etnomatematika Permainan Tradisional Sunda sebagai Media Pembelajaran Matematika - Irawan, Ari; Rahayu, Wanti; Nuzulah, Rahnita (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2023)
This study aims to identify the ethnomathematical elements found in traditional games, especially in Sundanese culture in West Java. The method used in this study is Research and Development with the Borg and Gall model with several stages: potential problems, gathering information, product design, design testing, design improvements, product trial, product revision, usage trial, and mass product manufacturing. This paper presents only at the stage of collecting information related to traditional Sundanese games that contain ethnomathematical elements. The results showed that there are traditional Sundanese games that have ethnomathematical elements. The games include bebentengan, hahayaman, congklak, ucing sumput (petak kumpet), Sunda manda (engklek), congklak, patok lele, kelereng, and gasing. These traditional games are usually played by elementary and junior high school age children, classified based on the type of ethnomathematics that are suitable for mathematics learning materials at the elementary and junior high school education unit levels.